Juristic theorizing of the provisions of Islamic law (the draftJaafari Status Law, as a model) - Inst. Dr. Rafid Hasan Majeed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Several questions come to mind when the subject of jurisprudential theory and theorizing is defined and studied, including what is the position of Islamic law on this theorizing? What rulings in Sharia can be theorized and which cannot? The call for a jurisprudential theorizing of the provisions of Islamic law is a call consistent with the goals and objectives of the Sharia calling for the negation of embarrassment, as it contains an orientalism for the future of Islamic law.I have decided, after seeking the help of God Almighty, to tackle the subject of jurisprudential theorizing of the provisions of Islamic law. This is because the call for jurisprudential theorizing came in response to a renewal in the contemporary jurisprudence movement, and is linked to life and the era in which we live.